Kinematics of judo backward breakfall: comparison between novice and experienced judokas - Koshida, S.; Matsuda, T.; Ishii, T.; Hashimoto, T. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
This study aimed to investigate the kinematic differences in judo backward breakfall between novice and experienced judokas. Eleven experienced and 13 novice judokas volunteered to participate in the study. Three-dimensional kinematic data were collected while participants performed five sets of backward breakfalls. We documented head-, neck-, trunk-, hip-, and knee-angle-time-curve profiles during judo breakfalls. The results showed significant differences in knee- and trunk-angle time curves, whereas no significant differences were found in head, neck, and hip kinematics between the novice and experienced judokas. These results suggest that motion of the lower extremity requires more attention during the learning of breakfall technique by novice judokas.